2005
DOI: 10.1085/jgp.200509417
|View full text |Cite
|
Sign up to set email alerts
|

Separate Ion Pathways in a Cl−/H+ Exchanger

Abstract: CLC-ec1 is a prokaryotic CLC-type Cl−/H+ exchange transporter. Little is known about the mechanism of H+ coupling to Cl−. A critical glutamate residue, E148, was previously shown to be required for Cl−/H+ exchange by mediating proton transfer between the protein and the extracellular solution. To test whether an analogous H+ acceptor exists near the intracellular side of the protein, we performed a mutagenesis scan of inward-facing carboxyl-bearing residues and identified E203 as the unique residue whose neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
334
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(350 citation statements)
references
References 29 publications
15
334
1
Order By: Relevance
“…One observation offered tentative support for our hypothesis. In prokaryotic ClC anion/ H þ exchange proteins a glutamate residue, corresponding to E203 in ClC-ec1, forms an essential part of the H þ transport pathway 36 . This residue is present on helix H, which forms the pseudo-symmetrical dimer interface ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One observation offered tentative support for our hypothesis. In prokaryotic ClC anion/ H þ exchange proteins a glutamate residue, corresponding to E203 in ClC-ec1, forms an essential part of the H þ transport pathway 36 . This residue is present on helix H, which forms the pseudo-symmetrical dimer interface ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From comparison with the mechanism proposed by Feng et al 13 for proton transport in ClC antiporters, it is possible that protonation of E232 in this conformation leads to opening of the common gate and H þ transport from the intracellular to the extracellular solution 2,30 . The H þ transport pathway of ClC-1 is unknown, as the intracellular glutamate residue proposed to form the intracellular H þ transport pathway in Cl À /H þ antiporters 36 is not conserved in ClC channels ( Supplementary Fig. S1).…”
Section: Discussionmentioning
confidence: 99%
“…In CLC channels, this glutamate residue is important for gating, whereas in exchangers the same residue is fundamental for the coupling between H C and Cl K . It has been shown that CLC exchangers present an additional glutamate in a position equivalent to position 203 of CLCec-1, which is not present in the channel subtype (Accardi et al 2005). Electrophysiological experiments have shown that the mutation of such glutamate abolishes the coupling with chloride (Accardi et al 2005).…”
Section: Towards Structure-function Analyses Of Plant Clcsmentioning
confidence: 99%
“…1). The reversal potential (51 mV) of the ''strained'' dimer 207C-207C is slightly lower, but this value still represents respectably tight exchange coupling, especially when compared with variously uncoupled mutants previously described (11,15,16). We conclude, then, that the normal mechanism of Cl Ϫ /H ϩ transport is unperturbed in the covalent-dimer constructs.…”
Section: Resultsmentioning
confidence: 56%